A War on Cops? The Effects of Ferguson on the Number of U.S. Police Officers Murdered in the Line of Duty. (29th July 2017) - Maguire, Edward R.; Nix, Justin; Campbell, Bradley A.
Abstract : Police agencies in the U.S. are currently facing a major legitimacy crisis resulting from a spate of high-profile use of force incidents, many involving minority citizens. Recent headlines emphasize that there is now a "war on cops" and that police officers are facing increasing levels of hostility and violence fueled by a growing anti-police sentiment. In the aftermath of events in Ferguson, Missouri in August 2014, some commentators claim that the number of police officers feloniously assaulted and killed in the line of duty has increased sharply. Using time series analysis of data from the Officer Down Memorial Page, we test whether events in Ferguson were associated with an increase in the number of police officers murdered in the line of duty. Our results provide no evidence for a "Ferguson Effect" on the number of U.S. police officers murdered in the line of duty as of March 2016.